Spatial Planning and its Need for National and Regional Bibliographies of Grey Literature. Issue 1 (2nd January 2019) - Erlinger, Christian
Abstract: National bibliographies provide interesting opportunities to search for new publications in specific scientific disciplines. This article gives an overview about the bibliographic potential of National Bibliographies in the German-speaking countries for spatial planning both in research and practice. Because grey literature plays an important role in technical disciplines, a national bibliography is a worthwhile source for information retrieval. Furthermore, this article includes a lightweight python-script to parse the bibliographic information from literature relevant to spatial planning and to measure the importance of grey literature using the SRU-API of the German National Library.